The effect of wide resection during radical prostatectomy on surgical margins - Lavallée, Luke T.; Stokl, Andrew; Cnossen, Sonya; Mallick, Ranjeeta; Morash, Chris; Cagiannos, Ilias; Breau, Rodney H. (Canadian Urological Association Journal, 2016)
Introduction: The impact of nerve-sparing on positive surgical margins during radical prostatectomy (RP) remains unclear. The objective of this study was to determine the incidence of positive surgical margins with a wide resection compared to a nerve-sparing technique. Methods: A consecutive, single-surgeon patient cohort treated between August 2010 and November 2014 was reviewed. A standardized surgical approach of lobe-specific nerve-spare or wide resection was performed. Lobe-specific margin status and tumour stage were obtained from pathology reports. Univariable and multivariable associations between nerve management technique and lobe-specific positive surgical margin were determined. Results: Of 388 prostate lobes, wide resection was performed in 105 (27%) and nerve-sparing in 283 (73%). In 273 lobes without extra-prostatic extension (EPE), 0 of 52 (0%) had a positive margin when wide resection was performed compared to 20 of 221 (9%) if nerve-sparing was performed (p=0.02). In 115 lobes with EPE, 11 of 53 (21%) had a positive margin if wide resection was performed compared to 28 of 62 (45%) if nerve-sparing was performed (p=0.006). In multivariable analysis, the risk of a positive margin was decreased among patients who received wide resection as compared to nerve-spare (RR 0.43, 95% CI 0.26‒0.71; p=0.001). Conclusions: Surgical techniques to reduce positive surgical margins have become increasingly important as more patients with high-risk cancer are selecting surgery. The risk of a positive margin was greatly reduced using a standardized wide resection technique compared to nerve-sparing.